Symbols for Hijabs in The Proudest Blue The Story of Hijab and Family by Ibtihaj Muhammad and S.K. Ali - Riana Permatasari; Afina Murtiningrum (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
This study aimed at analyzing symbols that represent hijab as depicted in The Proudest Blue The Story of Hijab and Family written by Ibtihaj Muhammad and S.K. Ali and illustrated by Hatem Aly. This study was a qualitative study that analyze a text, so that the data were in the form of sentences and illustrations taken from the book. The data were collected by reading the book, identifying the data, and classifying the data. Then, the collected data were analyzed using the semiotic theory from Peirce. Based on the findings, there were five symbols representing hijab. The first two symbols are related to the authors’ choice of color. The author uses the pink to illustrate that hijabs are related to love and the blue color that is related to religious symbol of piety and chastity or sincerity. The blue color was the most dominant symbol in the book. In addition, the authors recommend that hijab is not a whisper, a laugh, and a tablecloth. These three symbols represent hijabs as something strong, not a joke to be laughed at and not only a thing to cover. All symbols used by the author are positive ones which challenge the negative stereotypes about hijab in which it is associated with radicalism and terrorism.